Preparation process of composite bone setting pill
By using multi-step fine treatment and advanced technical means in the preparation process of composite bone elixir, the problems of poor mixing uniformity, dissolution and stability in the existing processes are solved, and more efficient drug release and better therapeutic effects are achieved.
Patent Information
- Application Number
- CN202510186365.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-11
AI Technical Summary
The existing composite bone elixir preparation process has shortcomings in raw material pretreatment, mixing and processing, and modification treatment before pill forming, resulting in poor mixing uniformity, dissolution and stability of the drug.
Multi-step fine treatment such as ultrasonic oscillation, airflow crushing and ball milling are adopted, combined with technical means such as low-temperature plasma treatment, supercritical carbon dioxide extraction, electrostatic spraying, microwave drying, vacuum freeze-drying, magnetic field treatment, pulse electric field treatment and photocatalytic treatment, optimize the pretreatment, mixing and treatment process of raw materials, and improve the uniformity of the pills and drug release efficiency.
It significantly improves the mixing uniformity and dissolution of the drug, enhances the stability and bioavailability of the pills, and improves the treatment effect of the patients.
Smart Images

Figure BDA0005278626630000101 
Figure BDA0005278626630000111 
Figure BDA0005278626630000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of traditional Chinese medicine preparation, and in particular to a preparation process of a composite bone-setting pill. Background Art
[0002] In the field of traditional Chinese medicine, the optimization and improvement of the preparation process of compound bone-setting pills, as a fracture treatment drug with significant efficacy, has always been a hot topic of research. However, after an in-depth analysis of the existing preparation process, it is not difficult to find that there are still technical difficulties and challenges that need to be solved.
[0003] Traditional preparation processes generally lack fine-tuning of raw material characteristics during the raw material pretreatment stage, especially during the drying process. For example, if the temperature of angelica, saffron and other medicinal materials rich in active ingredients is not properly controlled or the drying time is too long, it is very easy to cause the loss of active ingredients, thereby affecting the efficacy of the drug. For medicinal materials with higher hardness, such as dragon bones and cinnabar, if the drying is not sufficient, it will directly affect the subsequent crushing effect and drug release performance.
[0004] In the mixing and processing stage, the existing process mainly relies on simple physical mixing and crushing methods, which makes it difficult to achieve sufficient and uniform mixing and efficient refinement of the raw materials. This will not only lead to uneven distribution of ingredients inside the pills, affecting the stability and uniformity of the drugs, but may also reduce the solubility of the drugs, thereby affecting the therapeutic effect of patients.
[0005] In addition, the current preparation process often ignores the in-depth modification of the mixed materials before pill molding. The application of advanced technical means such as low-temperature plasma treatment, supercritical carbon dioxide extraction, vacuum freeze drying, magnetic field treatment and pulsed electric field treatment can effectively improve the hardness, solubility and stability of pills, but these technologies have not been fully utilized in the existing process.
[0006] In summary, the existing preparation process of the composite bone-setting pill still has obvious deficiencies in raw material pretreatment, mixing and processing, and modification before pill molding. A more efficient and sophisticated preparation process is urgently needed to overcome these technical difficulties in order to prepare composite bone-setting pills with superior performance and more significant efficacy. Summary of the invention
[0007] Technical issues solved
[0008] In view of the above-mentioned shortcomings of the prior art, the present invention provides a preparation process of a composite bone-setting pill. The preparation process of the composite bone-setting pill of the present invention significantly improves the mixing uniformity and solubility of the drug. Through multi-step refinement treatments such as ultrasonic oscillation, airflow crushing and ball milling, the sufficient mixing and fineness of the raw materials are ensured, thereby improving the uniformity of the pills and the drug release efficiency. In addition, the application of low-temperature plasma treatment and supercritical carbon dioxide extraction further enhances the extraction and stability of the active ingredients of the drug, so that the preparation process shows significant advantages in improving the solubility and bioavailability of the drug, bringing better therapeutic effects to patients.
[0009] Technical Solution
[0010] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0011] A preparation process of a composite bone-setting pill, the preparation process comprising the following steps:
[0012] First, prepare raw materials, which include, by weight: 12-18 parts of angelica, 8-12 parts of saffron, 18-22 parts of dragon bones, 6-8 parts of cinnabar, 10-16 parts of catechu, 15-19 parts of natural copper, 8-14 parts of frankincense, 9-15 parts of myrrh, 12-16 parts of ginseng, 15-21 parts of raw dragon bones, 12-18 parts of oysters, 4-6 parts of realgar, 13-19 parts of earthworms, 5-7 parts of leeches, and 8-12 parts of earthworms;
[0013] Then, angelica, saffron, dragon bone, cinnabar, catechu, natural copper, frankincense, myrrh, ginseng, raw dragon bone, oyster, realgar, earthworm, leech and earthworm are pretreated respectively, and the pretreatment includes removing impurities, washing and drying, wherein the drying temperature of angelica is 38-42°C and the drying time is 3.5-4.5 hours, the drying temperature of saffron is 28-32°C and the drying time is 2.5-3.5 hours, the drying temperature of dragon bone is 43-47°C and the drying time is 4.5-5.5 hours, the drying temperature of cinnabar is 33-37°C and the drying time is 3.5-4.5 hours, the drying temperature of catechu is 48-52°C and the drying time is 2.5-3.5 hours, the drying temperature of natural copper is 53-57°C and the drying time is 3.5-4.5 hours, the drying temperature of frankincense is 5 The temperature is 38-42℃, and the drying time is 3.5-4.5 hours. The drying temperature of myrrh is 43-47℃, and the drying time is 2.5-3.5 hours. The drying temperature of ginseng is 33-37℃, and the drying time is 4.5-5.5 hours. The drying temperature of raw dragon bone is 48-52℃, and the drying time is 3.5-4.5 hours. The drying temperature of oyster is 53-57℃, and the drying time is 2.5-3.5 hours. The drying temperature of realgar is 38-42℃, and the drying time is 3.5-4.5 hours. The drying temperature of earthworm is 43-47℃, and the drying time is 4.5-5.5 hours. The drying temperature of leech is 33-37℃, and the drying time is 3.5-4.5 hours. The drying temperature of earthworm is 38-42℃, and the drying time is 2.5-3.5 hours.
[0014] Next, the pretreated angelica, saffron, dragon bone, cinnabar, catechu, natural copper, frankincense, myrrh, ginseng, raw dragon bone, oyster, realgar, earthworm, leech, and earthworm are mixed according to the above weight portions to obtain a mixture, and the mixture is placed in an ultrasonic oscillation device, and is treated with ultrasonic oscillation at a frequency of 20-30kHz and a power of 100-200W for 10-20 minutes to further mix the raw materials evenly;
[0015] Afterwards, the mixed material after ultrasonic oscillation treatment is put into a jet mill for pulverization, the pulverizing chamber pressure of the jet mill is 0.35-0.45 MPa, the pulverizing medium is compressed air, the pressure of the compressed air is 0.45-0.55 MPa, and the pulverizing time is 18-22 minutes to obtain a mixed powder;
[0016] The mixed powder is then put into a ball mill for ball milling, the speed of the ball mill is 350-450 rpm, the ball milling time is 3.5-4.5 hours, the ball milling medium is agate balls, the diameter of the agate balls is 6-8 mm, and the filling rate of the agate balls is 45%-55% of the volume of the ball mill to obtain refined powder;
[0017] Subsequently, the refined powder is put into a blender, and a binder is added, wherein the weight of the binder is 6%-8% of the weight of the refined powder, and the binder is starch paste. The starch paste is prepared by mixing starch and water in a weight ratio of 1:6-1:7, heating to 65-75° C., stirring evenly, and cooling to room temperature to obtain starch paste, wherein the stirring speed of the blender is 250-350 rpm, and the stirring time is 25-35 minutes, to obtain a viscous mixed material;
[0018] Finally, the viscous mixture is put into a pill-making machine to make pills. The working temperature of the pill-making machine is 23-27° C. and the pill-making speed is 60-80 pills / minute to obtain the composite bone-setting pills.
[0019] Furthermore, before the mixed material is placed in the ultrasonic oscillation device, the mixed material is also subjected to a step of low-temperature plasma treatment. The power of the low-temperature plasma treatment is 300-500W, the treatment time is 5-10 minutes, and the treatment gas is a mixture of helium and oxygen, wherein the volume ratio of helium to oxygen is 3:1-5:1.
[0020] Furthermore, before the refined powder is put into the blender, the step of subjecting the refined powder to supercritical carbon dioxide extraction is also included. The pressure of the supercritical carbon dioxide extraction is 20-30MPa, the temperature is 40-50°C, and the extraction time is 1-2 hours. After the extraction, the extract is obtained by vacuum separation, and the extract is mixed with the refined powder and then put into the blender.
[0021] Furthermore, after the pills are made by the pill making machine, the method further includes the step of electrostatically spraying the pills. The electrostatically sprayed coating is nano titanium dioxide, the coating concentration is 5%-10%, the electrostatic voltage is 30-50kV, the spraying time is 5-10 minutes, and the spraying distance is 10-15cm.
[0022] Furthermore, after the pills are made by the pill making machine, the method further comprises a step of subjecting the pills to microwave drying, wherein the microwave drying power is 600-700 W, the drying temperature is 35-45° C., the drying time is 2-4 hours, and the microwave frequency is 2450 MHz.
[0023] Furthermore, before the viscous mixed material is placed into the pill making machine, the mixed material is also subjected to a step of vacuum freeze drying, wherein the vacuum degree of the vacuum freeze drying is 0.03-0.05MPa, the freezing temperature is -30°C to -40°C, the freezing time is 3-5 hours, and then the mixed material is dried for 2-4 hours at a temperature of 30-40°C and a vacuum degree of 0.06-0.08MPa.
[0024] Furthermore, before the viscous mixed material is placed into the pill making machine, the mixed material is subjected to a magnetic field treatment step, wherein the magnetic field strength is 0.5-1.0 T and the treatment time is 10-20 minutes.
[0025] Furthermore, before the viscous mixed material is placed into the pill making machine, the mixed material is subjected to a pulse electric field treatment step, wherein the pulse electric field has an intensity of 10-20 kV / cm, a pulse width of 10-20 μs, a pulse frequency of 100-200 Hz, and a treatment time of 5-10 minutes.
[0026] Furthermore, after the pills are made by the pill making machine, the step of photocatalytically treating the pills is also included. The photocatalytic treatment uses ultraviolet light with a wavelength of 365-385nm and a photocatalytic time of 15-30 minutes. During the photocatalytic process, the pills are placed on a carrier coated with a titanium dioxide photocatalyst.
[0027] Beneficial Effects
[0028] Compared with the known public technology, the technical solution provided by the present invention has the following advantages:
[0029] Beneficial effects:
[0030] 1. The preparation process of the composite bone-setting pill of the present invention significantly improves the mixing uniformity of the raw materials through multiple steps such as fine raw material pretreatment, ultrasonic oscillation, airflow crushing, ball milling, etc., especially the ultrasonic oscillation treatment, which can promote the mutual penetration and dispersion between the raw materials by high-frequency vibration, avoiding the problem of local uneven concentration that may exist in the traditional mixing method. At the same time, the airflow crushing and ball milling process further refines the raw material particles, increases the contact area between the drug and the dissolution medium, and thus improves the solubility of the drug. This preparation process significantly improves the solubility of the composite bone-setting pill in simulated human gastric juice, which helps to enhance the absorption and utilization efficiency of the drug in the body.
[0031] 2. This patent introduces a variety of post-processing steps in the preparation process, such as low-temperature plasma treatment, supercritical carbon dioxide extraction, electrostatic spraying, microwave drying, vacuum freeze drying, magnetic field treatment, pulse electric field treatment and photocatalytic treatment. These steps not only further improve the purity and activity of the drug, but also significantly optimize the physical properties of the pills. Among them, vacuum freeze drying can retain the original structure of the drug to the maximum extent and avoid drug denaturation caused by high-temperature drying; magnetic field and pulse electric field treatment may enhance its stability by changing the arrangement and orientation of drug molecules. In addition, electrostatic spraying forms a uniform nano-titanium dioxide coating on the surface of the pills, which not only improves the appearance quality of the pills, but also enhances its anti-moisture and anti-oxidation properties, thereby extending the shelf life of the drug. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Example 1
[0035] (I) Raw material preparation:
[0036] Prepare the raw materials according to weight: 15 parts of angelica, 10 parts of saffron, 20 parts of dragon bones, 7 parts of cinnabar, 13 parts of catechu, 17 parts of natural copper, 11 parts of frankincense, 12 parts of myrrh, 14 parts of ginseng, 18 parts of raw dragon bones, 15 parts of oysters, 5 parts of realgar, 16 parts of earthworms, 6 parts of leeches, and 10 parts of earthworms.
[0037] (II) Raw material pretreatment:
[0038] Each raw material is subjected to impurity removal, cleaning and drying treatment. Angelica is dried at 40°C for 4 hours; saffron is dried at 30°C for 3 hours; dragon bone is dried at 45°C for 5 hours; cinnabar is dried at 35°C for 4 hours; catechu is dried at 50°C for 3 hours; natural copper is dried at 55°C for 4 hours; frankincense is dried at 40°C for 4 hours; myrrh is dried at 45°C for 3 hours; ginseng is dried at 35°C for 5 hours; raw dragon bone is dried at 50°C for 4 hours; oyster is dried at 55°C for 3 hours; realgar is dried at 40°C for 4 hours; earthworm is dried at 45°C for 5 hours; leech is dried at 35°C for 4 hours; earthworm is dried at 40°C for 3 hours.
[0039] (III) Mixing and processing:
[0040] The pretreated raw materials were mixed to obtain a mixture, which was placed in an ultrasonic oscillation device and subjected to ultrasonic oscillation treatment at a frequency of 25 kHz and a power of 150 W for 15 minutes.
[0041] The mixed material after ultrasonic oscillation treatment was put into a jet mill, the crushing chamber pressure was set to 0.4 MPa, and compressed air with a pressure of 0.5 MPa was used as the crushing medium. The mixed powder was obtained by crushing for 20 minutes.
[0042] The mixed powder was put into a ball mill, the rotation speed was adjusted to 400 rpm, and the ball milling was performed for 4 hours. The ball milling medium was agate balls with a diameter of 7 mm, and the filling rate was 50% of the volume of the ball mill to obtain a refined powder.
[0043] Prepare starch paste as a binder, mix starch and water in a weight ratio of 1:6.5, heat to 70°C, stir evenly, and cool to room temperature. Take 7% of the weight of the refined powder, add the starch paste to the refined powder, put it into a blender, and stir at a speed of 300 rpm for 30 minutes to obtain a viscous mixed material.
[0044] The viscous mixture is placed in a pill-making machine, the operating temperature of the pill-making machine is set at 25° C., and the pill-making speed is 70 pills / minute to make pills.
[0045] Example 2 (adding low temperature plasma treatment)
[0046] (I) Raw material preparation and pretreatment:
[0047] Same as Example 1.
[0048] (ii) Mixing and processing:
[0049] The pretreated raw materials were mixed to obtain a mixed material, which was first treated with a low-temperature plasma at a power of 400 W for 8 minutes, with the treatment gas being a mixed gas of helium and oxygen (volume ratio 4:1), and then placed in an ultrasonic oscillation device for 15 minutes at a frequency of 25 kHz and a power of 150 W. The subsequent steps were the same as in Example 1.
[0050] Example 3 (adding supercritical carbon dioxide extraction treatment)
[0051] (I) Raw material preparation and pretreatment:
[0052] Same as Example 1.
[0053] (ii) Mixing and processing:
[0054] After obtaining the refined powder according to the steps of Example 1, the refined powder was subjected to supercritical carbon dioxide extraction treatment, the pressure was set to 25 MPa, the temperature was 45° C., the extraction was performed for 1.5 hours, and the extract was separated under reduced pressure after the extraction, and the extract was mixed with the refined powder. The subsequent steps of adding a binder, stirring, and pelleting were the same as in Example 1.
[0055] Embodiment 4 (addition of electrostatic spraying treatment)
[0056] (I) Raw material preparation and pretreatment, mixing and pelleting:
[0057] The pills were prepared according to the steps of Example 1.
[0058] (ii) Post-processing:
[0059] The pills were electrostatically sprayed with a nano titanium dioxide coating having a concentration of 8%, an electrostatic voltage of 40 kV, a spraying time of 8 minutes, and a spraying distance of 12 cm.
[0060] Example 5 (addition of microwave drying treatment)
[0061] (I) Raw material preparation and pretreatment, mixing and pelleting:
[0062] The pills were prepared according to the steps of Example 1.
[0063] (ii) Post-processing:
[0064] The pills were subjected to microwave drying treatment, with a microwave drying power of 650 W, a drying temperature of 40° C., a drying time of 3 hours, and a microwave frequency of 2450 MHz.
[0065] Example 6 (adding vacuum freeze drying treatment)
[0066] (I) Raw material preparation and pretreatment, mixing and pre-pill making steps:
[0067] The steps of Example 1 were followed until a viscous mixture was obtained.
[0068] (II) Mixed material processing and pelleting:
[0069] The mixed material was subjected to vacuum freeze-drying treatment with a vacuum degree of 0.04 MPa, a freezing temperature of -35°C, and a freezing time of 4 hours. It was then dried at a temperature of 35°C and a vacuum degree of 0.07 MPa for 3 hours. The mixture was then placed in a pill-making machine with the operating temperature of the pill-making machine set to 25°C and a pill-making speed of 70 pills / minute to make pills.
[0070] Embodiment 7 (adding magnetic field treatment)
[0071] (I) Raw material preparation and pretreatment, mixing and pre-pill making steps:
[0072] The steps of Example 1 were followed until a viscous mixture was obtained.
[0073] (II) Mixed material processing and pelleting:
[0074] The mixed material was subjected to magnetic field treatment with a magnetic field intensity of 0.8 T for 15 minutes, and then put into a pill-making machine with an operating temperature of 25° C. and a pill-making speed of 70 pills / minute to make pills.
[0075] Embodiment 8 (adding pulse electric field treatment)
[0076] (I) Raw material preparation and pretreatment, mixing and pre-pill making steps:
[0077] The steps of Example 1 were followed until a viscous mixture was obtained.
[0078] (II) Mixed material processing and pelleting:
[0079] The mixed material was subjected to pulse electric field treatment with a pulse electric field strength of 15 kV / cm, a pulse width of 15 μs, a pulse frequency of 150 Hz, and a treatment time of 8 minutes. The mixed material was then placed in a pill making machine with the operating temperature of the pill making machine set at 25°C and a pill making speed of 70 pills / minute to make pills.
[0080] Example 9 (adding photocatalytic treatment)
[0081] (I) Raw material preparation and pretreatment, mixing and pelleting:
[0082] The pills were prepared according to the steps of Example 1.
[0083] (ii) Post-processing:
[0084] The pills were subjected to photocatalytic treatment using ultraviolet light with a wavelength of 375 nm for 20 minutes. During the photocatalytic process, the pills were placed on a carrier coated with a titanium dioxide photocatalyst.
[0085] Comparative Example 1 (without ultrasonic oscillation treatment)
[0086] (I) Raw material preparation and pretreatment:
[0087] Same as Example 1.
[0088] (ii) Mixing and processing:
[0089] The pretreated raw materials are directly mixed to obtain a mixed material, and the ultrasonic oscillation treatment step is skipped. The subsequent air flow crushing, ball milling, adding a binder, stirring, and pelletizing steps are the same as in Example 1.
[0090] Comparative Example 2 (without airflow crushing treatment)
[0091] (I) Raw material preparation and pretreatment:
[0092] Same as Example 1.
[0093] (ii) Mixing and processing:
[0094] The pretreated raw materials are mixed and then subjected to ultrasonic oscillation treatment, and then the air flow crushing step is skipped, and the mixed material after ultrasonic oscillation treatment is directly ball milled, and the subsequent steps are the same as in Example 1.
[0095] Comparative Example 3 (without ball milling)
[0096] (I) Raw material preparation and pretreatment:
[0097] Same as Example 1.
[0098] (ii) Mixing and processing:
[0099] The pretreated raw materials are mixed and then subjected to ultrasonic oscillation and air flow pulverization treatment to obtain a mixed powder, and the ball milling step is skipped. The binder is directly added, stirred, and pelletized. The subsequent steps are the same as in Example 1.
[0100] Comparative Example 4 (Changing Adhesive)
[0101] (I) Raw material preparation and pretreatment:
[0102] Same as Example 1.
[0103] (ii) Mixing and processing:
[0104] The steps of Example 1 are followed to obtain a mixed powder, the binder is replaced with gelatin (7% by weight of the refined powder), added to the mixed powder, and stirred at 300 rpm for 30 minutes. The subsequent pilling steps are the same as in Example 1.
[0105] Performance test and result comparison:
[0106] (I) Test items and methods:
[0107] Pill hardness test: Use a hardness tester to measure the hardness of the pills. Test 10 pills for each sample and take the average value.
[0108] Drug dissolution test: Use a dissolution tester to determine the solubility of the drug in simulated human gastric juice according to the method specified in the "Chinese Pharmacopoeia". Sampling is performed at specified time points (30min, 60min, 90min, 120min) and the cumulative dissolution is calculated.
[0109] Stability test: The pills were placed in an environment with a temperature of 40°C and a relative humidity of 75% for accelerated aging for 3 months, and the changes in appearance were observed and the changes in the content of the active ingredient were detected.
[0110] (II) Test results:
[0111]
[0112]
[0113]
[0114] It can be seen from the test results that Examples 1-9 are better than Comparative Examples 1-4 in terms of pill hardness, drug solubility and stability. The low-temperature plasma treatment of Example 2 and the supercritical carbon dioxide extraction treatment of Example 3 have certain advantages in improving solubility and stability; the electrostatic spraying treatment of Example 4 and the photocatalytic treatment of Example 9 also have a certain improvement effect on the performance of the pills; the microwave drying treatment of Example 5, the vacuum freeze-drying treatment of Example 6, the magnetic field treatment of Example 7, and the pulsed electric field treatment of Example 8 optimize the comprehensive performance of the pills to varying degrees, while the lack of ultrasonic oscillation treatment in Comparative Example 1, the lack of airflow crushing treatment in Comparative Example 2, and the lack of ball milling treatment in Comparative Example 3 all lead to a decrease in pill performance. After the binder is changed, Comparative Example 4 also has a certain gap in solubility and stability compared with Example 1.
[0115] In summary, the composite bone-setting pill preparation process of the present invention can prepare bone-setting pills with excellent performance under the synergistic effect of various steps and treatment methods, and each improvement measure has a positive effect on the performance of the pills, providing an effective and stable process method for the preparation of bone-setting pills.
[0116] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A preparation process of a composite bone-setting pill, characterized in that: The preparation process comprises the following steps: First, prepare raw materials, which include, by weight: 12-18 parts of angelica, 8-12 parts of saffron, 18-22 parts of dragon bones, 6-8 parts of cinnabar, 10-16 parts of catechu, 15-19 parts of natural copper, 8-14 parts of frankincense, 9-15 parts of myrrh, 12-16 parts of ginseng, 15-21 parts of raw dragon bones, 12-18 parts of oysters, 4-6 parts of realgar, 13-19 parts of earthworms, 5-7 parts of leeches, and 8-12 parts of earthworms; Then, angelica, saffron, dragon bone, cinnabar, catechu, natural copper, frankincense, myrrh, ginseng, raw dragon bone, oyster, realgar, earthworm, leech and earthworm are pretreated respectively, and the pretreatment includes removing impurities, washing and drying, wherein the drying temperature of angelica is 38-42°C and the drying time is 3.5-4.5 hours, the drying temperature of saffron is 28-32°C and the drying time is 2.5-3.5 hours, the drying temperature of dragon bone is 43-47°C and the drying time is 4.5-5.5 hours, the drying temperature of cinnabar is 33-37°C and the drying time is 3.5-4.5 hours, the drying temperature of catechu is 48-52°C and the drying time is 2.5-3.5 hours, the drying temperature of natural copper is 53-57°C and the drying time is 3.5-4.5 hours, the drying temperature of frankincense is 5 The temperature is 38-42℃, and the drying time is 3.5-4.5 hours. The drying temperature of myrrh is 43-47℃, and the drying time is 2.5-3.5 hours. The drying temperature of ginseng is 33-37℃, and the drying time is 4.5-5.5 hours. The drying temperature of raw dragon bone is 48-52℃, and the drying time is 3.5-4.5 hours. The drying temperature of oyster is 53-57℃, and the drying time is 2.5-3.5 hours. The drying temperature of realgar is 38-42℃, and the drying time is 3.5-4.5 hours. The drying temperature of earthworm is 43-47℃, and the drying time is 4.5-5.5 hours. The drying temperature of leech is 33-37℃, and the drying time is 3.5-4.5 hours. The drying temperature of earthworm is 38-42℃, and the drying time is 2.5-3.5 hours. Next, the pretreated angelica, saffron, dragon bone, cinnabar, catechu, natural copper, frankincense, myrrh, ginseng, raw dragon bone, oyster, realgar, earthworm, leech, and earthworm are mixed according to the above weight portions to obtain a mixture, and the mixture is placed in an ultrasonic oscillation device, and is treated with ultrasonic oscillation at a frequency of 20-30kHz and a power of 100-200W for 10-20 minutes to further mix the raw materials evenly; Afterwards, the mixed material after ultrasonic oscillation treatment is put into a jet mill for pulverization, the pulverizing chamber pressure of the jet mill is 0.35-0.45 MPa, the pulverizing medium is compressed air, the pressure of the compressed air is 0.45-0.55 MPa, and the pulverizing time is 18-22 minutes to obtain a mixed powder; The mixed powder is then put into a ball mill for ball milling, the speed of the ball mill is 350-450 rpm, the ball milling time is 3.5-4.5 hours, the ball milling medium is agate balls, the diameter of the agate balls is 6-8 mm, and the filling rate of the agate balls is 45%-55% of the volume of the ball mill to obtain refined powder; Subsequently, the refined powder is put into a blender, and a binder is added, wherein the weight of the binder is 6%-8% of the weight of the refined powder, and the binder is starch paste. The starch paste is prepared by mixing starch and water in a weight ratio of 1:6-1:7, heating to 65-75° C., stirring evenly, and cooling to room temperature to obtain starch paste, wherein the stirring speed of the blender is 250-350 rpm, and the stirring time is 25-35 minutes, to obtain a viscous mixed material; Finally, the viscous mixture is put into a pill-making machine to make pills. The working temperature of the pill-making machine is 23-27° C. and the pill-making speed is 60-80 pills / minute to obtain the composite bone-setting pills.
2. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: Before the mixed material is placed in the ultrasonic oscillation device, the mixed material is also subjected to a step of low-temperature plasma treatment. The power of the low-temperature plasma treatment is 300-500W, the treatment time is 5-10 minutes, and the treatment gas is a mixed gas of helium and oxygen, wherein the volume ratio of helium to oxygen is 3:1-5:
1.
3. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: Before the refined powder is put into the mixer, the method also includes a step of subjecting the refined powder to supercritical carbon dioxide extraction treatment. The supercritical carbon dioxide extraction pressure is 20-30MPa, the temperature is 40-50°C, and the extraction time is 1-2 hours. After the extraction, the extract is obtained by decompression separation, and the extract is mixed with the refined powder and then put into the mixer.
4. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: After the pills are made by the pill making machine, the method further includes the step of electrostatically spraying the pills. The electrostatically sprayed coating is nano titanium dioxide, the coating concentration is 5%-10%, the electrostatic voltage is 30-50kV, the spraying time is 5-10 minutes, and the spraying distance is 10-15cm.
5. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: After the pills are made by the pill making machine, the method further comprises the step of subjecting the pills to microwave drying treatment, wherein the microwave drying power is 600-700W, the drying temperature is 35-45°C, the drying time is 2-4 hours, and the microwave frequency is 2450MHz.
6. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: Before the viscous mixed material is placed in the pill making machine, the mixed material is also subjected to a step of vacuum freeze drying. The vacuum degree of the vacuum freeze drying is 0.03-0.05MPa, the freezing temperature is -30°C to -40°C, the freezing time is 3-5 hours, and then the mixed material is dried for 2-4 hours at a temperature of 30-40°C and a vacuum degree of 0.06-0.08MPa.
7. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: Before the viscous mixed material is put into the pill making machine, the mixed material is subjected to a magnetic field treatment step, wherein the magnetic field intensity is 0.5-1.0T and the treatment time is 10-20 minutes.
8. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: Before putting the viscous mixed material into the pill making machine, the mixed material is subjected to a pulse electric field treatment step. The pulse electric field has an intensity of 10-20 kV / cm, a pulse width of 10-20 μs, a pulse frequency of 100-200 Hz, and a treatment time of 5-10 minutes.
9. The preparation process of the composite bone-setting pill according to claim 1, characterized in that: After the pills are made by the pill making machine, the method also includes a step of photocatalytically treating the pills. The photocatalytic treatment uses ultraviolet light with a wavelength of 365-385nm and a photocatalytic time of 15-30 minutes. During the photocatalytic process, the pills are placed on a carrier coated with a titanium dioxide photocatalyst.